Spatiotemporal evolution of air-sea CO2 flux in the Northwest Pacific and its response to ENSO - Shi, Haiyi; Chen, Ying; Gao, Hui (Frontiers in Marine Science, 2024)
Global warming, driven by human activities since the Industrial Revolution, has significantly elevated atmospheric carbon dioxide (CO2) levels, leading to higher global temperatures and a rise in extreme weather events. The ocean, as a major carbon sink, has absorbed about 30% of human-induced carbon emissions, helping mitigate global warming’s impacts. This study examines the spatiotemporal distribution of air-sea CO2 flux in the Northwest Pacific from 1982 to 2021 and its response to El Niño-Southern Oscillation, using Empirical Orthogonal Function and composite analysis. The seasonal patterns of air-sea CO2 flux and the influence of environmental factors were further evaluated. The results show that air-sea CO2 flux in the Northwest Pacific exhibits clear seasonal fluctuations. In winter, high-latitude areas act as significant carbon sources. Strong winds deepen the mixed layer, promoting CO2 release from the ocean into the atmosphere. In contrast, in summer, longer daylight hours, rising SST, and melting sea ice lead to upwelling, which brings nutrients to the surface and stimulates phytoplankton growth. This process turns the region into a carbon sink as phytoplankton growth, driven by intense sunlight, enhances the ocean’s CO2 absorption. The mid-latitude region consistently acts as a carbon sink year-round. During El Niño events, more negative air-sea CO2 flux anomalies appear in the eastern Northwest Pacific, enhancing carbon uptake. La Niña events have the opposite effect in the eastern regions. These findings highlight the Northwest Pacific’s critical role in modulating regional and global carbon cycles under varying climatic conditions. Understanding these dynamics is crucial for improving predictions of future climate impacts and for developing effective strategies to mitigate global warming.